(untitled) (Global Journal of Human-Social Science, 2018)
Background The learning developer guarantees in the student the active appropriation and creator of the knowledge and prepares it to solve the problems that are presented in its professional practice Objective To design didactic actions guided to achieve a learning developer in university students Methods Was carried out a traverse descriptive study in the understood period of October 2017 to October 2018 it was applied a not structured interview and a questionnaire to students of Medicine and it was used mathematical methods for the absolute and relative values Results It was verified that in the process teaching learning from the first year in the career of Medicine features of the teaching memoristic are used Conclusions The students recognized not to know how to identify the essential of the content they have difficulties to still apply it before new situations with the books of texts